G367(P) A service evaluation of the transition hub: facilitating transition from paediatric into adult palliative care. (25th October 2020) - Hosking, G; Baba, M
Abstract : Background: Increasing numbers of children with life limiting conditions are surviving into adulthood, resulting in more patients entering adult palliative care services. The transition process is crucial for ongoing care and resulting health outcomes. The Transition Hub is a charity-funded, time-limited project providing a holistic one stop service, hosted at adult hospices, to help support children and families in the process of transitioning into adult palliative care services. Aims: To evaluate the Transition Hub service to assess engagement, identify its user perceived strengths and areas for improvement. Methods: Quantitative analysis of data gathered on the existing transition database and qualitative analysis of the service user feedback were carried out to evaluate the impact of the service. Results: 38.5% of patients invited attended with 66% of attendees completing the feedback form. Overall, responses were positive, with 100% of respondents confirming that the Transition Hub addressed their concerns and queries. Identified areas of improvement included altering the time of clinic, more informative invitation letter and additional, varied medical support. Conclusion: The Hub is achieving its aims of guiding patients and families through the transition process. Some achievable improvements can be made to the future Hub service delivery. This model of service delivery during the transition process may be adopted by or of interest to other hospices and trusts.